The impact of comorbidities on the prognosis of patients with septic arthritis - Akhtar, Muhammad Umair; Chilmeran, Zaid; Sharafeldin, Abu-Baker Khalid; Waly, Yahya Mostafa; Khan, Mustafa Tariq; Fredericks, Salim (Frontiers in Medicine, 2025)
Septic arthritis is a serious infection that can lead to joint destruction, sepsis, and high mortality rates, particularly in elderly patients and those with comorbid conditions. Comorbidities such as diabetes, rheumatoid arthritis, chronic kidney disease, and liver disease can complicate the diagnosis, treatment, and overall prognosis of the disease. These conditions may impair immune function, delay diagnosis, and hinder effective antimicrobial therapy, thereby increasing the risk of severe complications and poor outcomes. This review explores the impact of comorbidities on the prognosis of patients with septic arthritis, emphasizing the need for tailored management strategies to improve outcomes in this vulnerable population. Understanding the interplay between comorbid conditions and septic arthritis is essential for optimizing treatment approaches and enhancing patient care.